PENGARUH TARIF PAJAK, TUNNELING INCENTIVE, MEKANISME BONUS, DAN KEPEMILIKAN ASING TERHADAP TRANSFER PRICING (Studi Empiris Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2014-2016) - Suci Asral Sukma; Vince Ratnawati; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of tax rates, tunneling incentive, bonus mechanisms, and foreign ownership on transfer pricing of the companies listed on Indonesia Stock Exchange in 2014-2016. The Ppulation of this study one all of the companies which is listed in Indonesian stock exchange. A total of the companies meet the sampling criterias. Data of this study was analyzed by using multipile regression method trough SPSS version 25. The results showed that tax rates and tunneling incentive affect the transfer pricing, while the bonus mechanisms and foreign ownership did not affect the tranfer pricing in the companies.Keywords : tax rates, tunneling incentive, bonus mechanisms, foreign ownership, transfer pricing